A Review on Modified Polymers and Their Composites - Irina DĂNĂILĂ (ȚÎCĂU); Tamara APARECI (GÎRNEȚ); Sebastian Marian DRĂGHICI; Iulian PĂDURARU; Gabriel SĂRACU; Adrian CÎRCIUMARU; Mihaela-Claudia GOROVEI (The Annals of “Dunarea de Jos” University of Galati. Fascicle IX, Metallurgy and Materials Science, 2022)
The main objective of this paper is to realise a review on fundamental research regarding the development of new and efficient methods to determine the mechanical, thermal, tribological, and thermo-mechanical properties of composite materials, analysing the results obtained through various graphs and diagrams accompanied by demonstrations and explanations from the specialized literature. Developing new materials or improving the properties of existing materials has been and is a concern of researchers. The chemistry of complex combinations represents one of the most important fields of scientific research, both in terms of theoretical investigations and practical applications. The interest shown towards complex combinations is justified by the contribution brought by the accumulation of knowledge about inorganic chemicals, polymers as well as about epoxy resins and polyvinyl ester, of course also about the design, formation and analysis through mechanical tests (compression, tension, three-point bending), thermal, tribological of composite materials modified with various modifying agents.